Biochemical thermodynamics : - Alberty, Robert A. (Wiley-Interscience, 2006)
This sequel to Robert Alberty's popular Thermodynamics of Biochemical Reactions describes how researchers will find Mathematica(r) a simple and elegant tool, which makes it possible to perform complex calculations that would previously have been impractical. Biochemical Thermodynamics: Applications of Mathematica(r) provides a comprehensive and rigorous treatment of biochemical thermodynamics using Mathematica(r) to practically resolve thermodynamic issues.